A RETROSPECTIVE STUDY ON EXTRACTION OF ROOT STUMP IN PATIENTS UNDER 35 YEARS AGE - G., Anjana; R.N. , Balakrishna (International Journal of Psychosocial Rehabilitation, 2020)
Root stumps are conditions where the crown structure is missing due to fracture and only the root is present in the socket. The most common causes include extensive untreated dental caries and negligence in seeking dental care. This can cause infections if left untreated. Hence, it is very important to get a root stump extracted. The aim of this study is to evaluate the incidence of root stump extraction in patients under 35 years of age visiting a dental hospital. All root stump case sheets were downloaded from Dental Information Archiving System (DIAS) software, verified, and copied to Microsoft Excel. Statistics were analyzed in SPSS software, and results were obtained. The total number of patients who underwent root stump extractions was 1695. Patients under 35 years of age numbered 68. Within the limits of this study, it can be concluded that the incidence of root stump extraction was higher in females than in males, and it is negatively correlated with age.